Trauma and Recovery in Oscar Hokeah’s Calling for a Blanket Dance: A Caruthian Reading - Apriyadi, Denny (Morphosis: Journal of Literature, 2025)
This study aims to examine the traumatic experiences and recovery process of the main character in Calling for a Blanket Dance (2023) by Oscar Hokeah. The novel follows Ever Geimausaddle, a Native American protagonist, as he navigates cycles of pain, resilience, and eventual healing. Through a multi-perspective narrative structure, Ever’s life is shaped by repeated encounters with trauma, rooted in both personal and cultural histories. This research employs a qualitative approach with a descriptive method to analyze narrative and dialogic elements from the novel. Drawing on Cathy Caruth’s (1996) trauma theory, the study investigates how trauma is represented and processed throughout the text. The findings reveal that Ever’s experiences align with four key symptoms of trauma: flashbacks, nightmares, intrusive thoughts, and avoidance. These symptoms manifest across various stages of his life, affecting his psychological state and interpersonal relationships. Furthermore, the study identifies several pathways to recovery portrayed in the novel, including the role of community support, reconnection with family, and the healing potential of storytelling. These coping mechanisms are central to Ever’s gradual healing and highlight the importance of culturally rooted resilience. Ultimately, the novel illustrates not only the enduring impact of trauma but also the transformative potential of collective healing and narrative expression. This research contributes to literary trauma studies by offering insight into Indigenous trauma narratives and the culturally embedded practices that foster recovery.